Analysis of Tourist Satisfaction Index Based on Structural Equation Model. (11th June 2022) - Peng, Yan; Jiang, Xiaolin
Abstract : In the modern economy and society, traveling abroad has gradually become one of the ways for people to enjoy life. With the continuous development of tourism and the change of tourists' consumption concepts, tourists' satisfaction has been received by more and more tourism managers and operators. It pays attention to providing tourism products and services from the perspective of tourists and meets the personalized and diversified needs of tourists. Tourist satisfaction has become an important indicator to measure the level of tourism in a tourist destination. According to the structural equation model, this paper constructs the tourist satisfaction index analysis index, which can truly and efficiently detect the tourist satisfaction index, which is convenient for the scenic spot to find out the areas that need to be improved, and enhance the new attraction and service level of the scenic spot. The research results of the article show that (1) there is no significant difference in the satisfaction of tourists of different genders. In terms of influencing factor indicators, individual factors have not passed the T test. The difference in satisfaction of tourists of different ages is not obvious, but there are also individual factors that do not pass the significance test in terms of influencing factors. For the actual perceived quality, the observation index with a larger contribution rate to principal component 2 is mainly the tourists' evaluation of the satisfaction of the tourist attractions. (2) The test result of the structural equation-based satisfaction analysis model proposed in the article is the highest among the four models. According to the error curve, it can be concluded that with the increasing complexity of the data, for the other three models, the evaluation error of the tourist satisfaction evaluation model is getting larger and larger, and the errors of the models proposed in the article are basically controlled within 0.4. Therefore, it can be concluded that the satisfaction evaluation model based on structural equations can reduce the error of tourist satisfaction.